Propriedade e renda fundiária: configurações contemporâneas do rural paulista - Reis de Souza, Tainá (2013)
The objective of this study was to understand the current relations of rent of land for sugarcane production in São Manuel and Barra Bonita - SP, with the guiding hypothesis that the current relationship between property and land rent keeps the agrarian question as pertinent issue in the understanding of what is termed as a new brazilian rural and that the current social relations of production and property present in rural areas are also expressions of the contemporary rural metamorphoses. From the research objectives, it was decided for a methodology of qualitative basis, with direct observation and unsystematic, and semi-structured interviews. The literature was reviewed, which pervaded themes as agrarian question in Brazil, new ruralities and land rent. In documentary research was conducted survey of municipal institutional records of the land uses, identifying genres produced and the quantity and size of farms. During the fieldwork were interviewed small farmers who rent or have rented - partially or completely - their lands for growing sugarcane, and representatives of the main rural local institutions. It was reported that due to the great regional demand of sugarcane and the difficulties in maintaining other crops, most growers began to devote himself to the production of sugarcane. This transition took place in the 60 and 70 - precisely the period of greatest State action on the sugarcane industry, with the policy of credits and other incentives. Later, with the need for mechanical harvesting and the use of more advanced technology, the maintenance of small sugarcane suppliers became more difficult. For this reason, and also due to the aging of the producers and the lack of interest of the heirs to maintain production, the rent of properties for mills or major producers of sugarcane appeared as a "solution". During the research it was discovered that in fact it not rent of land, but agricultural partnership. In the case studied smallholder cede their land for a large sugarcane agribusiness unit, for whom the partnership, and not the purchase of the land, it becomes more advantageous. It is stated that in this case the partnership do not appear as a remnant of past relationships, but as an expression of relations metamorphosed. With the presence of almost total rent properties is rare to have smallholder farmers, they are, in fact, small owners, who for years even live in the properties. The owners hold title of the land, but only in the legal form. The economic property of the soil, in other words, the appropriation of the economic excess of land, belongs to the mill partner. This theme is not only present in contemporary rural, but also a sign of its metamorphoses. As a final consideration it can be said that facing the transformations which the rural past has in recent decades, the issue of land rent appears as one more factor that should be considered. The debate that has guided the transformation of rural areas does not question the presence of land rent - even the agrarian question. In such a way that the changes concerning the relations between property and land rent are part of the rural areas and also point the metamorphosis of the contemporary rural.